PERTIMBANGAN PEMILIHAN STRATEGI PEMBELAJARAN SEJARAH DENGAN ORIENTASI STUDENT ACTIVE LEARNING DI SMA - Moch. Dimas Galuh Mahardika (Jurnal Pendidikan Sejarah Indonesia, 2021)
Today’s, learning paradigm has begun to be directed at student activities become learning centres. History learning, which is identical to the teacher’s domination with the lecture method, has begun to be transformed into empowering independently learning students activities, the goal is oriented towards student active learning. To implement this idea, it’s necessary to develop a history learning strategy expected to be achieved that goal. In developing learning strategies that are oriented towards student activities, some basic considerations that are elements in history learning must be considered to provide great opportunities for students to build their knowledge independently. This article is based on the study of literature, then produce an idea as a contribution to improving the quality of history learning.